THE EFFECT OF ISLAMIC POLITICAL KNOWLEDGE ON STUDENT ENGAGEMENT IN CAMPUS’ POLITICS - Sri Anggraeni; Riyadh Ahmad Faridz; Nova Nurul Putri; Farah Wardatul Zanah; Hisny Fajrussalam (Politea : Jurnal Politik Islam, 2021)
This study aims to determine how big the influence of Islamic political knowledge on student involvement in campus politics. The variables used in this study are knowledge of Islamic politics and student involvement in politics (a case study on Telecommunication System students at UPI Campus of Purwakarta Region). This research was conducted using quantitative methods with survey methods. The sampling technique used is Non Probability Sampling in which each member of the population has the same opportunity to be selected as a sample. The number of samples selected were 30 respondents from the Telecommunications System students of UPI Purwakarta Regional Campus batch 2019 - 2020. The data collection technique used was using a questionnaire and data analysis using SPSS version 21 software. Based on the individual parameter significance test (t-test) the results of the data obtained that t-count > t-table (3.965 > 1.701) which means Ha is accepted and Ho is rejected, it shows that Islamic political knowledge has an effect on student involvement in campus politics with a moderate correlation coefficient level of 60%. Based on the analysis of the coefficient of determination (R2), the R square value of 0.360 (36%) is determined by the effectiveness of Islamic political knowledge, while the remaining 64% is determined by other variables. The results of this study provide empirical evidence that Islamic political knowledge has an effect on student involvement in campus politics (a case study of students of the UPI telecommunications system at the Purwakarta campus).